Generalized self-driven AC-DC synchronous rectification techniques for single- & multiphase systems - Zhong,WX; Ho,WC; Hui,SYR (2010 International Power Electronics Conference Ecce Asia IPEC 2010, 2010)
This paper extends the single-phase self-driven synchronous rectification (SDSR) technique to multiphase and multi-level AC-DC systems. Power MOSFETs with either voltage or current self-sensing and self-driven gate drives are used to replace diodes in the rectifier circuits. The generalized methodology allows multiphase SDSRs to be designed to replace multiphase diode rectifiers. Unlike traditional SR designed for high-frequency power converters, the SDSR proposed here can be direct replacement of power diode bridges for both low and high frequency operations. The SDSR utilizes its output dc voltage to power its control circuit. No start-up control is needed because the body diodes of the power MOSFETs provide the diode rectifier for initial start-up stage. The generalized method is demonstrated in 2kW 1-phase and 3-phase SDSRs. Power loss reduction in the range of 50% to 69% has been achieved for inductive, capacitive and resistive loads. © 2010 IEEE.